2007
DOI: 10.3168/jds.2006-666
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Somatic Cell Count and Quarter Milk Flow Patterns

Abstract: Milk flow parameters at udder and quarter levels were studied in relation to somatic cell count (SCC) and other risk factors for mastitis (bimodality, duration of decline, and duration of overmilking phase). Thirty-eight Holstein cows in their first to sixth lactations were investigated during 10 mo of lactation. Monthly milk samples were collected for SCC during morning milking. Quarter and udder milk flows were recorded daily. A cow was included if one quarter was found to have an SCC higher than 200 x 10(3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 16 publications
2
40
0
Order By: Relevance
“…Godden et al (2003) also verified a decrease in SCC values during postpartum of nimals treated with intramammary seal. High SCC at calving is related to reduction in milk production (Green et al 2007, Tancin et al 2007, reinforcing the importance of using internal seal as a limiting factor to the entry of microorganism in the udder and in the control of new infections (Berry & Hillerton 2002, Godden et al 2003, Berry & Hillerton 2007, Parker et al 2007. Animals that have infections caused by coliforms could remain with a high SCC, due to the persistence of inflammatory reaction after bacterial cure, which may occur spontaneously (Smith et al 1985, Akers & Thompson 1987.…”
Section: Table 4 Rate Of New Infection and Chronicity Between Contromentioning
confidence: 99%
“…Godden et al (2003) also verified a decrease in SCC values during postpartum of nimals treated with intramammary seal. High SCC at calving is related to reduction in milk production (Green et al 2007, Tancin et al 2007, reinforcing the importance of using internal seal as a limiting factor to the entry of microorganism in the udder and in the control of new infections (Berry & Hillerton 2002, Godden et al 2003, Berry & Hillerton 2007, Parker et al 2007. Animals that have infections caused by coliforms could remain with a high SCC, due to the persistence of inflammatory reaction after bacterial cure, which may occur spontaneously (Smith et al 1985, Akers & Thompson 1987.…”
Section: Table 4 Rate Of New Infection and Chronicity Between Contromentioning
confidence: 99%
“…Using 200,000 cells mL -1 SCC threshold, Schepers et al (1997) found 74% sensitivity and 89% specificity in Holstein cows. Anatomical characteristics of teats have positive correlation with milk flow rate during milking that could be used for precocious identification of udder health problems which could increase the risks of mastitis (Tancin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Tancin et al (2007) studied the milk flow and its variations during lactation and observed influences in the somatic cell counts (SCC), as much as the udder as the individual teats. Generally, a SCC threshold of 200,000 cells mL -1 are recommended as the limit to separate uninfected mammary quarters from the infected ones, to decrease the occurrence of false-negative and false-positive results (Schepers et al, 1997;Djabri et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It indicated an unbalanced milk secretion between the four udder quarters. Quarters with long tAB had higher SCC in comparison with quarters with shorter tAB (Tančin et al 2007b). Lactation did not influence tAN (Tančin et al 2006), which is similar to the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…According to Naumann & Fahr (2000), the transition between tPL and tAB represented the moment on which the milk flow at least in one udder quarter has ended. The tAB is the time interval in which the full milking vacuum has an effect on one or more empty quarters (Tančin et al 2007b). Especially front quarters needed usually less time for milking than rear quarters because rear quarters contain more milk , Wellnitz et al 1999.…”
Section: Discussionmentioning
confidence: 99%